Effect of age on information security awareness level among young internet users in Malaysia - Omar, Siti Zobidah; Kovalan, Krishnapriyaa; Bolong, Jusang (Human Resource Management Academic Research Society, 2021)
The negligence to take proper security precautions while using the Internet has been lacking nowadays, especially among youth. Although youth deal the most with smart gadgets, past research has found that there is still lack of information security awareness among them. This can be shown by the number of cybercrimes arising day by day such as, cyberbullying, phishing, hacking, online threats, virus attacks, and so on. Thus, research has been conducted using quantitative methods by utilising a questionnaire to measure the information security awareness level among youth in Malaysia. The aim of this study is to determine the effect of age on the information security awareness level among young Internet users in Malaysia. 400 respondents have been participated in this survey. The findings of this study reveals that there is strong significant relationship between age (18-20 years old; 21-30 years old; 31-40 years old) and information security awareness (password usage, data protection, and data backup). Besides, there is no significant relationship between age and personal data sharing. However, respondents from 21-30 years old showed more concern towards information security awareness in this study. It is highly recommended for young Internet users to identify online threats and be aware of the security breaches encountered.